FEBI (Focused Interaction-Based Education) Education Model with Application in Blood Glucose Control in Type 2 Diabetes Mellitus Patients - Febriyanti; Masrul; Najirman; Indrapriyatna, Ahmad Syafruddin; Yunir, Em; Mudjiran; Semiarty, Rima; Yulia, Dwi (proceedinginternational, 2025)
Background: Optimal blood glucose control is the main key to preventing complications of type 2 Diabetes Mellitus (DM). However, many patients have difficulty maintaining glycemic control due to limited knowledge, ongoing education and lack of therapeutic interaction. The FEBI Education Model (Focused Interaction-Based Education) is designed to increase patient engagement through an interactive educational approach based on digital applications. Objective: This study was to test the effectiveness of the FEBI Education Model in helping control blood glucose in patients with type 2 DM. Method: The study used a quasi-experimental design with a one-group Pretest-Posttest design approach. With a sample of 30 patients with type 2 DM in the working area of Andalas Health Center and Ambacang Kuranji Health Center, with a purposive sampling technique and data analysis using Paired T-test samples. The FEBI model integrates self-education, glucose monitoring, medication reminders, and online consultative interaction features. The main parameters measured were changes in knowledge and attitudes and glycated albumin levels during one month of intervention. Results: The results of the study showed that there was an increase in knowledge and attitudes with a p-value of 0.00 and a decrease in glycated albumin levels with a -value of 0.025, statistically it can be concluded that there is an influence of the FEBI education model with an increase in knowledge and attitudes and a decrease in glycated albumin levels. Conclusion: The application-based FEBI Education Model is effective in improving blood glucose control in patients with type 2 DM. This interactive approach has the potential to be an innovative strategy in supporting technology-based diabetes management. Keywords: Type 2 Diabetes Mellitus, Interactive Education, Mobile Application, Blood Glucose Control